HUBUNGAN ANTARA REGULASI EMOSI DENGAN FEAR OF MISSING OUT(FoMO) PADA GEN Z PENGGUNA MEDIA SOSIAL TIKTOK DI YOGYAKARTA - Muhidin, Nurul Izza; Feno, Michael Yulian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to examine the relationship between emotion regulation and Fear of Missing Out among Generation Z TikTok users in Yogyakarta. Fear of Missing Out emerges as a psychological response to intensive social media use and is characterized by a strong desire to remain continuously connected to online social activities. This study employed a quantitative approach with a correlational design. The participants were Generation Z individuals who actively use TikTok and reside in Yogyakarta, with data collected through an online questionnaire measuring emotion regulation and Fear of Missing Out. Data analysis was conducted to identify the association between the two research variables. The results indicate that there is no significant relationship between emotion regulation and Fear of Missing Out among Generation Z TikTok users in Yogyakarta. These findings suggest that individuals’ ability to regulate emotions is not associated with the level of Fear of Missing Out they experience. Therefore, Fear of Missing Out among Generation Z TikTok users may be influenced by other factors beyond emotion regulation, such as individual characteristics or patterns of social media use. This study implies that understanding Fear of Missing Out requires consideration of additional variables relevant to the social media context of Generation Z